A 3-year follow-up of antibody response in HIV-infected children with immune recovery vaccinated with inactivated Japanese encephalitis vaccine - Puthanakit T. (2014)
Among HIV-infected children who had immune recovery after received antiretroviral therapy (ART), good responses to revaccination with childhood vaccines have been observed. However, the rate of long-term persistence of antibody response remains unknown. The objective of this study is to determine whether HIV-infected children still have protective antibody against Japanese encephalitis virus (JE) 3 years after receiving revaccination with two doses of inactivated JE vaccine. Plasma JE neutralizing antibody titer was determined by a plaque reduction neutralization assay. An antibody titer of more than 1:10 was defined as being protective. Fifty HIV-infected children with a mean age of 10.3 years (SD 2.2) and mean CD4 percentage of 25 (SD 5) were revaccinated with two doses of inactivated JE vaccine. Forty-three children had been followed-up for 3 years. The JE neutralizing antibody at 1 month and 3 years after revaccination were detected among 38 (88%) and 35 (81%) children, respectively. The geometric means titer significantly dropped from of 306 (min 13-max 163,617) to 106 (min 11-max 4645). This data show that the majority of HIV-infected children had persistent antibody 3 years after revaccination. JE revaccination in HIV-infected children with immune recovery after ART should be carried out in endemic areas. © 2010 Elsevier Ltd.